ACTIVITY OF ANTIOXIDANT COMPOUNDS IN DIFFERENT VARIETIES OF MANGO LEAVES - Lestari, Hartatik Sri; Wijayati, Nanik (Prodi Kimia, 2025)
Exposure to free radicals in the body in amounts that exceed normal limits can trigger the emergence of various diseases. The formation of free radicals can be inhibited or stopped using antioxidant compounds. Mango leaves are one of the natural materials known to contain secondary metabolite compounds such as flavonoids and phenolics that can be used as natural antioxidants. The writing of this article aims to determine the activity of the chemical compound in various kinds of mango leaves as a natural antioxidant to ward off free radicals based on literature review of the original articles conducted through a search engine with keywords antioxidant, mango leaves. The results of antioxidant activity of mango leaves as to free radical scavengers were obtained from 11 varieties, namely arumanis, bacang, gadung, gedong, kasturi, manalagi, podang, binjai, tandui, irwin, and machang pulasan. Mango leaves contain high secondary metabolite compounds that have potential as antioxidants with highly variable activity. The strongest results were shown in the mango gadung variety with an IC50 value of 3,263 ppm (very strong) using maceration method extraction with DPPH test. Factors that can affect the amount of bioactive compounds and antioxidant activity are the type of mango variety and growing location. Mango leaf as an antioxidant has the potential to be utilized for the food, cosmetic, and pharmaceutical industries.